Effect of heavy ions irradiation on LiTaO3 crystal - Lilong Pang (Results in Physics, 2021)
In this work, congruent LiTaO3 crystals are irradiated by heavy ions Fe, Xe, and Bi respectively at fluence range of 1 × 1012 ~ 2 × 1015 cm−2. The effects of heavy ions irradiation are studied by using optical transmission spectroscopy, Rutherford backscattering, optical microscopy, X-ray diffraction.Heavy ion irradiation presents a unique effect in transmission spectra which is quite opposite to the previous reported results of light ions irradiation. The latter could often cause a significant optical absorption in visible light region. The former, however, not only induce no optical absorption, but can enhance transmittance over a broad spectral range (340–2500 nm). It is found that the discrepancy may originate from different damage process during ions irradiation. Light ion irradiation can create numerous of simple defects (like oxygen vacancies) serving as color centers which can cause an optical absorption. However, direct amorphization dominates the damage process induced by heavy ions, during which it hardly produces simple defects. Moreover, due to direct heavy ions bombardment, special textures are formed on the surfaces of the samples which serve as antireflection structures and enhance optical transmissions.